National Crime Victimization Survey: Identity Theft Supplement, 2014 ([Verlag nicht ermittelbar], 2016)
The primary purpose of the Identity Theft Supplement is to obtain additional information about identity theft-related victimizations so that policymakers, academic researchers, practitioners at the Federal, state and local levels, and special interest groups who are concerned with identity theft can make informed decisions concerning policies and programs. Responses are linked to the NCVS survey instrument responses for a more complete understanding of the individual's circumstances.